Determinants of public transportation disability among older adults in China - Jiafeng Gu (Transport Policy, 2024)
Public transportation is important for older adults to meet their mobility needs and obtain external support. However, little is known about the elderly population with disabilities using public transportation. Using a nationally representative sample from the China Family Panel Studies (CFPS) for 2016, 2018, and 2020, we examined the elderly and public transportation disability (E&PTD) rate and its determinants in Chinese adults aged 45 years and above; the E&PTD rate in this population was 9.65%. The results showed that factors such as being female, age, and family size increased the likelihood of E&PTD in older adults. Married older adults with more education, better intelligence, higher incomes, receiving a pension, and living in urban areas and pilot provinces of healthcare reform were less likely to have E&PTD. This study provides an important policy reference for providing better public transportation services for E&PTDs.